2015
DOI: 10.3109/14767058.2014.1002764
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal outcomes of infants with gastroschisis: a 5-year follow-up in a tertiary referral center in Brazil

Abstract: Despite advances in perinatal care and surgical techniques, infants with gastroschisis still present high rates of complications and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…With the advances in neonatal medicine (neonatal intensive care units), management and repair, and parenteral nutrition since the 1960's [Nichol et al, ], survival of infants with gastroschisis has greatly improved. Contemporary survival rates range between 90% [Vachharajani et al, ] and 95% [Minutillo et al, ] in developed countries with lower survival in underdeveloped countries [Tarcă and Aprodu, ; Carvalho et al, ]. In this population‐based cohort of gastroschisis cases, overall infant mortality was low (4.4%).…”
Section: Discussionmentioning
confidence: 76%
“…With the advances in neonatal medicine (neonatal intensive care units), management and repair, and parenteral nutrition since the 1960's [Nichol et al, ], survival of infants with gastroschisis has greatly improved. Contemporary survival rates range between 90% [Vachharajani et al, ] and 95% [Minutillo et al, ] in developed countries with lower survival in underdeveloped countries [Tarcă and Aprodu, ; Carvalho et al, ]. In this population‐based cohort of gastroschisis cases, overall infant mortality was low (4.4%).…”
Section: Discussionmentioning
confidence: 76%
“…Many studies have demonstrated that the presence of a compromised bowel is associated with a significant increase in the number of surgical procedures, a longer period of full enteral feeding and a prolonged hospitalization [15,19] . Prolonged TPN, with its risk of sepsis, is directly related to intestinal recuperation, and the morbidity of GS is closely related to intestinal damage [20] . While gastrointestinal complications such as matting between the loops, malrotation, volvulus, perforations and atresia increase the complexity of early management [19,21] , later management may be complicated by the presence of problems of absorption, intestinal dysmotility, obstruction, NEC, infarction and stenosis [1,3,9] .…”
Section: Discussionmentioning
confidence: 99%
“…Blood group antigen is the second most common cause and happens mainly in infants with a mother of blood type O 2 . Sonographic features: Splenomegaly, hepatomegaly, polyhydramnios, echogenic bowel, pericardial effusion, skin, subcutaneous, pleural, peritoneal, scrotal, and placental oedema 3,4 are all sonographic appearances of fetal anaemia. However, the most reliable sign of fetal anaemia is increased peak systolic velocity of middle cerebral artery due to increased cardiac output and reduced blood viscosity 1 .…”
Section: Pr Bagloomentioning
confidence: 99%
“…Background: Occupational health and safety is increasingly becoming a focus of ultrasound departments due to the large number of injuries within the industry 1,2,3,4 . Ultrasound is considered a hazardous manual handling task, and with an increasing number of injuries seen in our workplace, our department created an Occupational Health and Safety team to address this problem 5 .…”
Section: S Matheis-hodges Monash Health Clayton Australiamentioning
confidence: 99%